Coming of age? Reflections on the centenary of women's admission to the Royal Geographical Society. Issue 4 (22nd October 2013) - Evans, Sarah L; Keighren, Innes M; Maddrell, Avril
Abstract : Women's admission to the Royal Geographical Society was at least a two‐staged affair, with a cohort of 22 women being admitted in 1892–93 before open access to women from 1913. However, whilst official membership was defined by these historic line‐in‐the‐sand 'boundary' moments, some aspects of women's participation within the Society were enacted in a permeable 'frontier zone'. Both prior to, and after, fully accessing Fellowship in 1913, women were active producers of geographical knowledge – travelling, researching, writing, and teaching. Given these blurred thresholds of participation and recognition, and the complex social politics of majority/minority views on women's access to full membership, marking and celebrating the centenary of women's admission to the Society is riddled with ambiguities. What is unambiguous, however, is that the centenary presents a long‐overdue opportunity to celebrate over a hundred years of women's geographical work. It also offers a moment to pause and reflect on the status of women within the discipline today.